1995
DOI: 10.1002/anie.199521221
|View full text |Cite
|
Sign up to set email alerts
|

[Mo154(NO)14O420(OH)28(H2O)70](25 ± 5)−: A Water‐Soluble Big Wheel with More than 700 Atoms and a Relative Molecular Mass of About 24000

Abstract: Complex clusters the size of small proteins can be generated in reduced molybdate solutions by linking defined fragments. An example of this is the giant cluster (NH4)25±5[Mo154(NO)14O420(OH)28(H2O)70]·ca. 350 H2O with a molar mass of more than 30000 gmol−1, the anion of which is shaped like a tire with a nanodimensional cavity more than 20 Å in diameter and has an extremely large inner and outer surface as well as a large number of mobile electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
186
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(187 citation statements)
references
References 4 publications
1
186
0
Order By: Relevance
“…Although the family of known molecular wheels is large, many of them incorporate less than 32 metal ions. The only exceptions to this include fMn 84 g reported by Christou et al (13), and the giant fMo 154 g reported by Müller et al (10), which are built up by early transition metal ions. The similarity between the fPd 84 g and fMn 84 g wheel in terms of nuclearity is remarkable, especially given the radically different subunit composition.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the family of known molecular wheels is large, many of them incorporate less than 32 metal ions. The only exceptions to this include fMn 84 g reported by Christou et al (13), and the giant fMo 154 g reported by Müller et al (10), which are built up by early transition metal ions. The similarity between the fPd 84 g and fMn 84 g wheel in terms of nuclearity is remarkable, especially given the radically different subunit composition.…”
Section: Resultsmentioning
confidence: 88%
“…In self-assembly, the observation of symmetrically favored numbers of metal nuclearity ("magic numbers") (6) or shapes with high symmetry, such as icosahedra (7) and rings (8)(9)(10), may provide a theoretical basis for the reliable and controlled fabrication of complex molecular architectures. In this respect we hypothesized that it is important to design minimal systems that use only a small number of chemical components, but with a vast library of possible architectures, and to use the techniques of structural and analytical chemistry to probe the range of accessible molecular architectures.…”
mentioning
confidence: 99%
“…Lastly, reduced POM clusters are related to molybdenum blue species and usually their composition is largely unknown with substantial ongoing research. The POM molecules that are central to this work are mostly symmetric HPAs including polyoxomolybdates (POMs) and polyoxotunstates (POWs), which consist of molybdenum (Mo) and tungsten (W) metals, respectively, and oxygen atoms in the form of metal oxide polyhedrons [38][39][40]. In POMs, all 12 MO 6 (or WO 6 ) units conforming to so-called Keggin structures are "outer" surface moieties.…”
Section: Introductionmentioning
confidence: 99%
“…They connect to the {Mo 8 and Browns. The most well-known Molybdenum Blue structures are the giant wheels, {Mo154} [27] and {Mo176} [28], and the {Mo132} Keplerate cluster [29], which are all constructed using the same structural building block, {MoMo5}. The central building block is occupied by a pentagonal bipyramidal {MoO7} unit, which is surrounded by five edge-shared {MoO6} octahedra along the equator of the bipyramid.…”
Section: Pom-based Clusters and Supramolecular Aggregatesmentioning
confidence: 99%